A new taxon for Dipteridaceae fronds from the Paso Flores formation, late Triassic, Neuquén basin, Argentina - Gnaedinger, Silvia Cristina (2020)
Fil: Gnaedinger, Silvia Cristina. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.